The Drosophila 7SK snRNP and the essential role of dHEXIM in development. - Nguyen, D.; Krueger, B.J.; Sedore, S.C.; Brogie, J.E.; Rogers, J.T.; Rajendra, T.K.; Saunders, A.; Matera, A.G.; Lis, J.T.; Uguen, P.; Price, D.H. (Nucleic Acids Research, 2012)
Regulation of the positive transcription elongation factor, P-TEFb, plays a major role in controlling mammalian transcription and this is accomplished in part by controlled release of P-TEFb from the 7SK snRNP that sequesters the kinase in an inactive state. We demonstrate here that a similar P-TEFb control system exists in Drosophila. We show that an RNA previously suggested to be a 7SK homolog is, in fact, associated with P-TEFb, through the action of a homolog of the human HEXIM1/2 proteins (dHEXIM). In addition, a Drosophila La related protein (now called dLARP7) is shown to be the functional homolog of human LARP7. The Drosophila 7SK snRNP (d7SK snRNP) responded to treatment of cells with P-TEFb inhibitors and to nuclease treatment of cell lysates by releasing P-TEFb. Supporting a critical role for the d7SK snRNP in Drosophila development, dLARP7 and dHEXIM were found to be ubiquitously expressed throughout embryos and tissues at all stages. Importantly, knockdown of dHEXIM was embryonic lethal, and reduction of dHEXIM in specific tissues led to serious developmental defects. Our results suggest that regulation of P-TEFb by the d7SK snRNP is essential for the growth and differentiation of tissues required during Drosophila development.